(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Placenta Previa (PP) is a significant cause of maternal and fetal morbidity and mortality, especially in patients with scared uterus. This study aimed to compare the maternal and neonatal outcomes of PP with and without coverage of a uterine scar in a tertiary hospital in Chattogram, Bangladesh. Materials and methods: A prospective observational study was conducted from January 2024 to June 2024 in Chittagong Medical College Hospital. Consecutively admitted 38 singleton pregnancies with PP with a history of Cesarean Section (CS) or myomectomy were included and divided into two groups: the PP with coverage of a uterine scar group (PPCS group) and the PP without coverage of a uterine group (Non-PPCS group). Maternal and neonatal outcomes between two groups were compared by statistical methods. Results: There were 38 patients with with PP on scared uterus and were further classified into two groups: PPCS (n=23) and Non-PPCS (n=18). Both the groups were comparable in terms of their baseline sociodemographic and clinical characteristics. Placenta accreta spectrum was (95.7% vs. 20%.0, p<0.001), hemorrgage (91.3% vs. 46.7%, p=0.006), urinary bladder injury (26.7% vs. 0%, p=0.031), peripartum hysterectomy (65.2% vs. 6.7%, p=0.001), ligation of uterine artery (56.5% vs. 93.3%, p=0.014) and use of uterine compression suture (30.4% vs. 66.7%, p=0.028) had a significant difference between PPCS group and Non-PPCS group. Neonatal outcomes in terms of prematurity, low birth weight, low APGAR score, need for NICU admission, and perinatal death were similar between two groups. Conclusion: The PPCS group had poorer maternal outcomes than the Non-PPCS group. To counsel their patients appropriately, healthcare providers should be aware of possible complications of placenta previa lying over the uterine scar. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 33-36